Brain abscess due to Listeria monocytogenes after HELLP syndrome in a patient with antiphospholipid syndrome. (August 2017) - Fervienza, A; Bodro, M; Castro, P; Hernández, S; Teixidó, I; Espinosa, G; Cervera, R
Objective: To illustrate an unusual case of Listeria cerebral abscess. Material and methods: A 32-year-old pregnant woman with thrombotic antiphospholipid syndrome (APS) received corticotherapy for two weeks due to hemolysis, elevated liver enzymes, low platelet (HELLP) syndrome. After delivery she presented with neurological symptoms and fever. Results: The MRI scan confirmed the presence of a brain abscess, and Listeria monocytogenes was isolated in blood cultures. After eight weeks of antibiotic treatment, the patient presented no sequelae. Conclusion: L. monocytogenes should be included in the differential diagnosis of patients with fever and neurological dysfunction, especially in those with a recent history of corticotherapy.